Relationship between tethered swimming in a flume and swimming performance - Ruiz-Navarro, J. J.; Morouço, P. G.; Arellano, R. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To study the relationship between tethered swimming in a flume at different speeds and swimming performance. Methods: Sixteen regional-level swimmers performed 25-, 50-, and 100-m front-crawl trials and four 30-s tethered-swimming tests at 0, 0.926, 1.124, and 1.389 m/s water-flow velocities. Average and maximum force, average and maximum impulse, and intracyclic force variation (dF) were estimated for each tethered-swimming trial. Swimming velocity and intracyclic velocity variation (dv) were obtained for each free-swimming trial. Stroke rate and rating of perceived exertion (RPE) were registered for all trials. Results: Tethered-swimming variables, both at 1.124 m/s and at 1.389 m/s water-flow velocities, were positively associated with 25-m swimming velocity (P<.05). Average force and maximum impulse in stationary swimming were significantly associated with 25-m swimming velocity (P<.05). A positive relationship between water-flow velocities with dF was observed. Swimming performance was not related to dF or dv. Neither stroke rate nor RPE differed between the 4 tethered conditions and mean 50-m free-swimming velocity (P>.05). Conclusions: Measuring force in a swimming flume at higher water-flow velocities is a better indicator of performance than stationary tethered swimming. It enables assessment of the ability to effectively apply force in the water.